Comparative Efficiencies of Traditionally Used Limes and Their Effects on Potassium and Sodium Release in a Moderately Acid Soil - Sanchary, Ishrat Jahan; Huq, Shah Muhammad Imamul (European Journal of Applied Sciences, 2022)
Introduction and purpose Intensive cultivation has resulted, among other adverse effects, in increasing soil acidity. Moreover, some soils are acidic by origin which ultimately limits the growth of most crops. Liming is a common practice to bring the soil pH to an optimum range (6.5-7.5) for plant growth. The use of different Ca-rich and Mg-rich limes is the usual practice and their liming capability depends on different factors. Methods In the present study, CaO, Ca(OH)2, CaCO3 and MgCO3 limes were used for 10 months period to evaluate their relative efficiencies to raise the pH to 6.5 or above and to figure out how they affect K and Na release in a moderately acid soil. Result and discussion It was observed that CaO was more efficient than the other liming materials to reach the desired pH. The change on soil pH also affected the K and Na levels of the soil. A positive impact of these limes on K availability was observed while the response on Na solubility was negative due to Ca-rich limes but positive for Mg-rich lime. Conclusion and suggestion CaO can be used for raising pH and ensuring K availability in soils, however, longer period field trial of the limes is needed to evaluate crop quality and disease infestation.